Pricing and Reimbursement of Biosimilars in Central and Eastern European Countries - Kawalec, Paweł; Stawowczyk, Ewa; Tesar, Tomas; Skoupa, Jana; Turcu-Stiolica, Adina; Dimitrova, Maria; Petrova, Guenka I.; Rugaja, Zinta; Männik, Agnes; Harsanyi, Andras; Draganic, Pero (Frontiers in Pharmacology, 2017)
Objectives: The aim of this study was to review the requirements for the reimbursement of biosimilars and to compare the reimbursement status, market share, and reimbursement costs of biosimilars in selected Central and Eastern European (CEE) countries. Methods: A questionnaire-based survey was conducted between November 2016 and January 2017 among experts from the following CEE countries: Bulgaria, Czech Republic (Czechia), Croatia, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Romania. The requirements for the pricing and reimbursement of biosimilars were reviewed for each country. Data on the extent of reimbursement of biologic drugs (separately for original products and biosimilars) in the years 2014 and 2015 were also collected for each country, along with data on the total pharmaceutical and total public health care budgets. Results: Our survey revealed that no specific criteria were applied for the pricing and reimbursement of biosimilars in the selected CEE countries; the price of biosimilars was usually reduced compared with original drugs and specific price discounts were common. Substitution and interchangeability were generally allowed, although in most countries they were at the discretion of the physician after a clinical assessment. Original biologic drugs and the corresponding biosimilars were usually in the same homogeneous group, and internal reference pricing was usually employed. The reimbursement status of biosimilars in the majority of the countries was the same and amounted to 100%. Generally, the higher shares of expenditures were shown for the reimbursement of original drugs than for biosimilars, except for filgrastim, somatropin and epoetin (alfa and zeta). The shares of expenditures on the reimbursement of biosimilar products ranged from 8.0% in Estonia in 2014 to 38.1% in Lithuania in 2015, and generally increased in 2015. The share of expenditures on reimbursement of biosimilars in the total pharmaceutical budget differed between the countries, with the highest observed for Hungary and the lowest – for Croatia. Conclusions: The requirements for the pricing and reimbursement of biosimilar products as well as the access of patients to biologic treatment do not differ significantly between the considered CEE countries. Biosimilar drugs significantly influence the reimbursement systems of these countries.